Left Ventricular Reconstruction and Mitral Valve Annuloplasty Combined with Papillary Muscle Relocation for Severe Ischemic Mitral Regurgitation - Furukawa, Koji; Yano, Mitsuhiro; Nakamura, Eisaku; Matsuyama, Masakazu; Nishimura, Masanori; Kawagoe, Katsuya; Nakamura, Kunihide (Scientific Research, 2017)
A 46-year-old man was referred to our hospital due to severe ischemic mitral regurgitation with severe bileaflet tethering and a dilated left ventricle. We performed left ventricular reconstruction and mitral valve annuloplasty combined with papillary muscle relocation. Although left ventricular continued remodeling occurred during follow-up, left ventricular reconstruction and mitral valve annuloplasty combined with papillary muscle relocation provided durable mitral repair, and his functional status was good. Thus, this combined surgical treatment may reduce mitral regurgitation recurrence after mitral valve annuloplasty.
Keywords: Ischemic Mitral Regurgitation; Left Ventricular Reconstruction; Mitral Valve Annuloplasty; Papillary Muscle Relocation